Beverage Impacts on Health and Nutrition Second Edition - Wilson, Ted; Temple, Norman J. (Nutrition and Health, 2016)
This comprehensive and authoritative second edition offers food scientists, nutritionists, public health specialists, and those involved in the research and development of new beverages an exhaustive survey of how common beverages impact our health and nutrition, as well as a basis for research designed to produce healthier beverages.   Every year brings an improvement in our understanding of how the many types and aspects of what we drink (beverages) impact our health and a desire to understand the current state of affairs for beverage technology.  There is still no new single book that provides objective reviews on the wide range of global health issues associated with alcoholic ad non-alcoholic beverages.  Beverage Impacts on Nutrition and Health, Second Edition is the single best source of reviews that describe beverage history; coffee, tea, alcohol, wine, cranberry and citrus juice, tea, coffee, dairy milk, soy milks and breast milk. Furthermore the book contains up-to-date reviews that describe beverage effects on satiety and energy balance, recommendations for persons with diabetes and metabolic syndrome, nutritional supplementation for the elderly, performance enhancement by athletes, energy drinks, and bottled water qualities. The final chapters summarize soft drink marketing issues, health effects of sugar and high fructose corn syrup, beverage ingredient functions, beverage labeling regulation and the importance of trends in beverage development.  These updated chapters are objectively written to emphasize peer-reviewed references and minimize the anecdotal references often seen in the current literature describing beverages and their impact on our health and nutrition.  All chapters are authored by recognized authorities from industry, the health-care system, and universities.  This book contains 24 concise and user-friendly chapters intended to enable readers to grasp the message quickly and easily. .